Geometric changes and mass balance of the Austfonna ice cap, Svalbard - G. Moholdt; J. O. Hagen; T. Eiken; T. V. Schuler (The Cryosphere, 2010)
The dynamics and mass balance regime of the Austfonna ice cap, the largest glacier on Svalbard, deviates significantly from most other glaciers in the region and is not fully understood. We have compared ICESat laser altimetry, airborne laser altimetry, GNSS surface profiles and radio echo-sounding data to estimate elevation change rates for the periods 1983–2007 and 2002–2008. The data sets indicate a pronounced interior thickening of up to 0.5 m y−1, at the same time as the margins are thinning at a rate of 1–3 m y−1. The southern basins are thickening at a higher rate than the northern basins due to a higher accumulation rate. The overall volume change in the 2002–2008 period is estimated to be −1.3±0.5 km3 w.e. y−1 (or −0.16±0.06 m w.e. y−1) where the entire net loss is due to a rapid retreat of the calving fronts. Since most of the marine ice loss occurs below sea level, Austfonna's current contribution to sea level change is close to zero. The geodetic results are compared to in-situ mass balance measurements which indicate that the 2004–2008 surface net mass balance has been slightly positive (0.05 m w.e. y−1) though with large annual variations. Similarities between local net mass balances and local elevation changes indicate that most of the ice cap is slow-moving and not in dynamic equilibrium with the current climate. More knowledge is needed about century-scale dynamic processes in order to predict the future evolution of Austfonna based on climate scenarios.